Enabling the Business of Agriculture 2016 : Comparing Regulatory Good Practices - World Bank Group (Washington, DC: World Bank, 2016)
Enabling the Business of Agriculture 2016 provides a tool for policy makers to identify and analyze legal barriers for the business of agriculture and to quantify transaction costs of dealing with government regulations.